1999
DOI: 10.1046/j.1365-2672.1999.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

The linamarase ofMucor circinelloidesLU M40 and its detoxifying activity on cassava

Abstract: Mucor circinelloides LU M40 produced 12·2 mU ml−1 of linamarase activity when grown in a 3 l fermenter in the following optimized medium (g l−1 deionized water): pectin, 10·0; (NH4)2SO4, 1·0; KH2PO4, 2·0; Na2HPO4, 0·7; MgSO4.7H2O, 0·5; yeast extract, 1·0; Tween‐80, 1·0, added after 48 h of fermentation. The purified linamarase was a dimeric protein with a molecular mass of 210 kDa; the enzyme showed optimum catalytic activity at pH 5·5 and 40 °C and had a wide range (3·0–7·0) of pH stability. The enzyme substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
2
4
0
Order By: Relevance
“…In addition, an increase in temperature leads to an increase in kinetic energy which causes denaturation and destabilization of thermostable threedimensional structure of the enzyme at high temperature Fadahunsi et al Bull Natl Res Cent (2020) 44:185 (Bisswanger 2014). However, Petrucciolli et al (1999) and Nwokoro and Onyebuchi (2011) reported that optimal linamarase activity of Mucor circinelloides and L. delbrueckii occurred at 40 °C and 50 °C, respectively, which is at variance with our findings in this investigation. It is pertinent to report that each enzyme has its own optimum temperature for activity which is dependent on the strength of amino acids as monomers of enzymes (Maherawati et al 2017).…”
Section: Discussionsupporting
confidence: 57%
“…In addition, an increase in temperature leads to an increase in kinetic energy which causes denaturation and destabilization of thermostable threedimensional structure of the enzyme at high temperature Fadahunsi et al Bull Natl Res Cent (2020) 44:185 (Bisswanger 2014). However, Petrucciolli et al (1999) and Nwokoro and Onyebuchi (2011) reported that optimal linamarase activity of Mucor circinelloides and L. delbrueckii occurred at 40 °C and 50 °C, respectively, which is at variance with our findings in this investigation. It is pertinent to report that each enzyme has its own optimum temperature for activity which is dependent on the strength of amino acids as monomers of enzymes (Maherawati et al 2017).…”
Section: Discussionsupporting
confidence: 57%
“…In our genome-wide analysis, three BGLs (GH3) were identified, of which two were predicted to be extracellular (protein IDs 33615 and 38405). This is consistent with previous reports of BGL from M. circinelloides , although it was not specifically identified and characterized in those studies [24], [31].…”
Section: Resultssupporting
confidence: 92%
“…Ikediobi and Onyike [31] and Okafor and Ejiofor [13] demonstrated that it is possible to reduce the cassava toxicity by the addition of an exogenous linamarase during the fermentation. Petruccioli et al [32], reported in 1999 that addition of Mucor circinelloides crude linamarase during cassava tuber fermentation shortened and enhanced the detoxification process leading to a complete hydrolysis of cassava cyanogenic glucoside. In contrast, Giraud et al [33] observed that inoculation of cassava pulp with a strain of lactic acid bacteria possessing a strong linamarase activity did not appear to contribute to cassava detoxification.…”
Section: Resultsmentioning
confidence: 99%